Development of genomic simple sequence repeat markers for Glycyrrhiza lepidota and cross-amplification of other Glycyrrhiza species - Jun Hyoung Bang (PeerJ, 2019)
Background Licorice (Glycyrrhiza spp. L.) is used as a natural sweetener and medicinal herb in European and Asian countries. Molecular studies have been conducted to find differences between wild and cultivated species because most wild species are highly resistant to abiotic and biotic stresses compared with their cultivated species. However, few molecular markers have been developed for studying the genetic diversity and population structure of licorice species and to identify differences between cultivars. Thus, the present study aimed to develop a set of genomic simple sequence repeat (SSR) markers for molecular studies of these species. Methods In the present study, we developed polymorphic SSR markers based on whole-genomesequence data of Glycyrrhiza lepidota. Then, based on the sequence information, the polymorphic SSR markers were developed. The SSR markers were applied to 23 Glycyrrhiza individual plants. We also evaluated the phylogenetic relationships and interspecies transferability among samples. Results The genetic diversity analysis using these markers identified 2–23 alleles, and the major allele frequency, observed heterozygosity, genetic diversity, and polymorphism information content were 0.11–0.91, 0–0.90, 0.17–0.94, and 0.15–0.93, respectively. Interspecies transferability values were 93.5%, 91.6%, and 91.1% for G. echinata, G. glabra, and G. uralensis, respectively. Phylogenetic analysis clustered cultivated (group 1) and wild (group 2) species into three and two subgroups, respectively. The reported markers represent a valuable resource for the genetic characteri z ation of Glycyrrhiza spp. for theanalysis of its genetic variability, and as a tool for licorice transferability. This is the first intraspecific study in a collection of Glycyrrhiza spp. germplasm using SSR markers.